Aspek Yuridis Risiko Gagal Bayar dan Overloan dalam Perjanjian Pinjam Meminjam Uang Berbasis Teknologi Informasi - Ardellia Novellita (Jurnal Hukum Lex Generalis, 2025)
Problems that often arise in Peer to Peer Lending are the risk of default and Over-indebtedness. This study aims to examine and analyze the legal consequences of the risk of default and excessive borrowing in information technology-based lending and borrowing agreements; to find out the implementation of risk mitigation and the use of the Financial Information Service System (SLIK) in P2P Lending. The legal consequences of default, namely the imposition of sanctions as stated in the agreement such as billing directly to the residence/office of the Loan Recipient, Billing through Emergency Contact Numbers, Giving subpoenas, filing civil lawsuits to the competent court and Reporting to government institutions/agencies. Meanwhile, the legal consequences related to over-indebtedness have no provisions that regulate it, both in agreements and national regulations; and Risk mitigation carried out, namely, First, requiring the Operator to strengthen credit scoring. Second, P2P Lending Operators must apply and adhere to prudential principles to prevent defaults and over-indebtedness. The use of the Financial Information Service System (SLIK) is deemed not to meet the material for credit scoring in P2P Lending, so a Fintech Data Center (FDC) is formed.